Profile of a Modern Hunter and the Socio-Economic Significance of Hunting in Poland as Compared to European Data - Krzysztof Kupren (MDPI AG, 2021)
Hunting is a unique form of activity in rural areas with a high proportion of forest areas, which involves nature conservation and meets social needs for recreation and the preservation of traditions while being an important part of economic activity. The presented study results, based on a literature review and questionnaire surveys conducted among hunters associated in hunting clubs in the north-eastern part of Poland, provide the basis for a discussion on the socio-economic significance of hunting, both in the country and throughout the European continent. Based on the results presented in the paper, it can be concluded that the number and density of hunters differ in individual countries. Moreover, hunting is practised in Europe by almost 7 million people, of which 127,000 are in Poland, and is a typical male activity. Most hunters in Poland and other European countries are professionally active inhabitants of rural areas, aged approximately 50 years, with several years of shooting experience and an income exceeding average values. Hunting is an important part of socio-economic activities, particularly in rural areas. It is estimated that in the EU alone, hunting can be worth approximately EUR 16 billion, and creates 100–120 thousand jobs. The most recent results of studies conducted in certain EU countries and the wide range of services provided by the hunting sector indicate that these values may be considerably higher. Regarding Poland, despite the centralised game resource management system, there are no extensive studies of the economic significance of hunting, and the official data are limited to a few basic indices related to hunting statistics. As indicated by the study results presented in this paper, in Poland, hunting-related expenditures are clearly lower than the European average and, thus, the economic significance of hunting is relatively low in this country. Despite this, it is a hunting community that, as a result of the adopted system solutions, is responsible for the functioning of reasonable game management while significantly affecting the management of the vast majority of rural areas.